Atenção à saúde da criança: programa nacional de melhoria do acesso e da qualidade na atenção básica no Estado do Ceará - Pinheiro, Maria Talyta Mota (2018)
The National Program for the Improvement of Access and Quality in Primary Care (PMAQ) is an eminent policy for the evaluation of basic care (AB), carried out by the Ministry of Health (MS) and has the participation of managers, health professionals and users of services . The areas of health, health and mental health, medical, medical, medical, hospital and medical-hospital are located after the end of the primary health care (PHC) course. The objective of this study was to evaluate the quality of life of the child in the 2nd cycle of the PMAQ in the State of Ceará. This is a cross-sectional, evaluative study to obtain data on the external evaluation in 2014. We searched 1626 health variables and the data are listed in tables with explanatory variables: macro-regions of the state, population, proportion of PDAQ in Ceará. The data were analyzed by descriptive and analytical statistics, respecting the ethical aspects. The indicators are distributed in equalization and synthesis teams, mostly an availability of inputs, printed materials and immunobiological. As the most accomplished actions were the following: registration of children with updated vaccines (99.5%) and household (97.4%). In the stratum evaluation, of the 16 items evaluated for growth and development monitoring, 11 the statistically significant investor, with inferior performance for stratification 1 or lower levels. In the analysis of groups, there was difference in population size and stratum, with better performance of municipalities with more than 100 thousand inhabitants. A demonstrative analysis was conducted in a child health consultation. In the end, evidences, even with the expansion of PHC, there are divergences between the regions of Ceará, generating heterogeneity in the quality of exercise, human resources and actions of actions. This promotes inequities in childcare, not reaching the principles of quality.